Diferenças de avaliação entre o Poder Judiciário e a ANS sobre a necessidade de oferecimento de home care nos contratos de plano de saúde - Santos, Ezequiel Fajreldines dos (2018)
This research explores judicial decisions about the home care services by health plan insurers and seeks to investigate if regulatory organs and the Judicial Power diverge about the obligatoriness of this service in heal plan contracts. For the analysis, was performed a research of the doctrine, all the decisions provided by the Agência Nacional de Saúde Suplementar (ANS) and by the Superior Tribunal de Justiça (STJ). The first chapter explains what are medical aid plans, their general characteristics and the regulation, creating an overview of the subject and the regulatory framework. The second chapter explores the ANS’ decisions, identifying the agency’s positioning e valuing its conformity to the regulatory framework. The third chapter covers decisions from STJ. In it, decisions and its justifications are analyzed. Finally, this works is concluded with the confrontation of the positions from ANS and from STJ. The conclusion is that the ANS and the STJ diverge about the necessity to offer the treatment: the ANS admits its exclusion, grounding its position in the possibility offered by the Health Plans’ Statue, while the STJ, invoking other normative precepts, determines that the home care must be offered. Beyond that, this research concludes that the divergence between regulators and the Judiciary Power may bring unwanted results to insured and insurers.